Magnetic-field effect on the photoactivation reaction of Escherichia coli DNA photolyase. - Henbest, K; Maeda, K; Hore, P; Joshi, M; Bacher, A; Bittl, R; Weber, S; Timmel, C; Schleicher, E (2008)
One of the two principal hypotheses put forward to explain the primary magnetoreception event underlying the magnetic compass sense of migratory birds is based on a magnetically sensitive chemical reaction. It has been proposed that a spin-correlated radical pair is produced photochemically in a cryptochrome and that the rates and yields of the subsequent chemical reactions depend on the orientation of the protein in the Earth's magnetic field. The suitability of cryptochrome for this purpose has been argued, in part, by analogy with DNA photolyase, although no effects of applied magnetic fields have yet been reported for any member of the cryptochrome/photolyase family. Here, we demonstrate a magnetic-field effect on the photochemical yield of a flavin-tryptophan radical pair in Escherichia coli photolyase. This result provides a proof of principle that photolyases, and most likely by extension also cryptochromes, have the fundamental properties needed to form the basis of a magnetic compass.